Editorial: acid suppression with potassium‐competitive acid blockers dismissing genotype concerns. Issue 1 (17th December 2020) - Scarpignato, Carmelo; Hunt, Richard H.
Abstract : LINKED CONTENT This article is linked to Hwang et al and Hwang & Lee papers. To view these articles, visit https://doi.org/10.1111/apt.16131 and https://doi.org/10.1111/apt.16158